2020
DOI: 10.1080/00207454.2020.1806267
|View full text |Cite
|
Sign up to set email alerts
|

Study on the ameliorating effect of miR-221-3p on the nerve cells injury induced by sevoflurane

Abstract: Purpose: Sevoflurane is a widely used anesthetics, however, it has been reported that sevoflurane has neurotoxic effects. Studies have shown that miR-221-3p can ameliorate neuron damage. This study was to investigate whether miR-221-3p could reduce the neurotoxic effect of sevoflurane on nerve cells. Materials and methods: The rat hippocampal neuron cells were treated with sevoflurane or cultured normally. And we constructed neuron cells that overexpressed or low expression of miR-221-3p in the presence or abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…However, this observation found that high postoperative plasma microRNA-221-3p level was independent risk factors for POCD, the mechanism may be related to its proinflammatory effect. With regards to the regulatory mechanism of microRNA-221-3p in related diseases, Wang et al found that microRNA-221-3p ameliorated sevoflurane-induced cell injury by promoting cellular activity and inhibiting apoptosis through suppression of CDKN1B expression [ 28 ]. Numerous studies implicated a relationship between microR-221-3p and inflammation, microRNA-221-3p could mediate the antitumor effects of IFN-α [ 29 ], microRNA-221-3p and microRNA-92a-3p are reportedly associated with smoking-induced inflammation in COPD (chronic obstructive pulmonary disease) [ 30 ], microRNA-221-3p could drive the shift of macrophages towards pro-inflammatory functions by inhibiting the activation of JAK3/STAT3 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this observation found that high postoperative plasma microRNA-221-3p level was independent risk factors for POCD, the mechanism may be related to its proinflammatory effect. With regards to the regulatory mechanism of microRNA-221-3p in related diseases, Wang et al found that microRNA-221-3p ameliorated sevoflurane-induced cell injury by promoting cellular activity and inhibiting apoptosis through suppression of CDKN1B expression [ 28 ]. Numerous studies implicated a relationship between microR-221-3p and inflammation, microRNA-221-3p could mediate the antitumor effects of IFN-α [ 29 ], microRNA-221-3p and microRNA-92a-3p are reportedly associated with smoking-induced inflammation in COPD (chronic obstructive pulmonary disease) [ 30 ], microRNA-221-3p could drive the shift of macrophages towards pro-inflammatory functions by inhibiting the activation of JAK3/STAT3 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors revealed that miR-221-3p suppresses the osteogenic differentiation of degenerated AFs [ 11 ]. It has also been reported that miR-221-3p can suppress cell apoptosis in several diseases [ 12 , 13 ], and excessive AF apoptosis is highly associated with IVDD progression [ 14 ]. Therefore, miR-221-3p may be a potent regulator that protects against IVDD.…”
Section: Introductionmentioning
confidence: 99%